2013
DOI: 10.4103/0300-1652.126283
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, awareness and practice regarding needle stick injuries in dental profession in India: A systematic review

Abstract: Background:Hundreds of thousands of healthcare workers remain susceptible to deadly viruses throughout the year, including blood-borne pathogens. Needle stick injuries (NSI) constitute one of the most common occupational health hazards in healthcare profession. Dental professionals are at more risk of acquiring NSI due to their limited and restricted working area. The present systematic review was carried out to determine knowledge, awareness and practice regarding NSI in dental professionals and students in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…[ 17 ] Taking into account all of the above, our results are consistent with the results of the systematic review conducted by Kapoor et al . [ 18 ] who showed that although the level of knowledge and awareness of dental students regarding the management of dental waste is adequate, it should be increased. Further studies with dentists and other dental professionals should be carried out, as there is little literature on the level of knowledge and awareness of dentists.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Taking into account all of the above, our results are consistent with the results of the systematic review conducted by Kapoor et al . [ 18 ] who showed that although the level of knowledge and awareness of dental students regarding the management of dental waste is adequate, it should be increased. Further studies with dentists and other dental professionals should be carried out, as there is little literature on the level of knowledge and awareness of dentists.…”
Section: Discussionmentioning
confidence: 99%
“…'s review. [ 47 ] This one is much more focused on needlestick injuries (NSI) among dental students, related knowledge level, awareness level regarding management of NSI and postexposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…There are many ways that disease can be transmitted, depending on the needle and the pathogens loaded in it. Previous articles revealed that every year around 3 million individuals got injured by NSI (Gambhir et al, 2013). Maximum care and precautions should be required to handle the needle or sharp objects.…”
Section: Introductionmentioning
confidence: 99%